2021
DOI: 10.3390/su13179619
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Influence of Information Systems on Sustainable Business Performance and Competitiveness

Abstract: The necessity for sustainable development, the coronavirus pandemic, and conducting business within the frameworks of the fourth industrial revolution—Industry 4.0 create a challenging environment where enterprises have difficulties to achieve and maintain competitiveness. Information is becoming a core construct when it comes to conducting business in the modern, globalized business environment. In this paper, the influence of information systems (IS) on sustainable business performance and competitiveness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
0
7
0
1
Order By: Relevance
“…Additionally to the competitiveness factors mentioned above, digitalization has become a critical factor for competitiveness recently. There is a rapid development of ICTs, which pressures enterprises to conduct business within the framework of the Fourth Industrial Revolution (Industry 4.0); with global markets and strong competition, some traditional manufacturing firms are implementing new maintenance innovations and policies, based on digitalization and a data-driven approach [4][5][6]. This further indicates that the application of modern information-communication technologies (ICTs) by enterprises is an important factor in sustainable development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally to the competitiveness factors mentioned above, digitalization has become a critical factor for competitiveness recently. There is a rapid development of ICTs, which pressures enterprises to conduct business within the framework of the Fourth Industrial Revolution (Industry 4.0); with global markets and strong competition, some traditional manufacturing firms are implementing new maintenance innovations and policies, based on digitalization and a data-driven approach [4][5][6]. This further indicates that the application of modern information-communication technologies (ICTs) by enterprises is an important factor in sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate, that enterprises have to evaluate their business processes and identify which can be improved via ICT solutions such as information systems, cloud infrastructure, etc. [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Next, an ARIMA graph that doesn't include the gender and environmental assessment predictors is presented (Figure 2). (Ćoćkalo et al, 2020;Kim et al, 2020a)  social entrepreneurship (Gupta et al, 2020)  attitudes and pillars of entrepreneurship (Liguori et al, 2020)  entrepreneurial economy (Youseff et al, 2021)  sustainable development (Cervelló-Royo et al, 2020)  sustainable business (Djalic et al, 2021)  sustainable growth (Kim et al, 2020b)  technological progress (Bakator et al, 2019)  Industry 4.0 (Bakator et al, 2018)  Industry 5.0 (Javaid & Haleem, 2020;Maddikunta et al, 2021)  the concept of Society 5.0 (Konno & Schillaci, 2021;Narvaez Rojas et al, Youth entrepreneurship has to be molded in a way that corresponds to the modern business environment. However, due to the globalization of markets, constant changes, and challenges, the core of youth entrepreneurship remains (innovation, value, and sustainability), but other aspects such as education, technology, and market dynamics have to be flexible from the entrepreneur's perspective.…”
Section: Youth and Entrepreneurship In Serbia -Challenges And Opportu...mentioning
confidence: 99%
“…According to Pappas et al ( 2018 ), sustainable development is one that meets the needs of the present without jeopardising the ability of future generations to meet their own needs in the same way. It is responsible for handling supply chain activities, materials, knowledge, and money to improve the supply chain profitability while reducing environmental effects and boosting the social quality of life (Djalic et al, 2021 ). Another factor affecting SCM is the increase in the number of new enabling technologies at different levels of the supply chain (Min et al, 2019 ; Queiroz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies (Ludbrook et al, 2019 ; Nia et al, 2021 ; Pappas et al, 2018 ) found that DSC strengthens the interaction and coordination between confidential global organisations and has coordinated the actions of allies with the help of software and information networks. Digitalisation enhances SCM’s sustainability by making it more accessible, practical, and cheap, according to the most recent and advanced theories given by Gupta et al, ( 2020a , 2020b ); Agrawal et al ( 2021 ); and Djalic et al ( 2021 ). They also highlighted that it shortens the material flow of goods and services and the skill, expertise, and capital required to manage it.…”
Section: Introductionmentioning
confidence: 99%